PENGEMBANGAN MEDIA BIG BOOK PADA MATERI KONDUKTOR SISWA KELAS V SEKOLAH DASAR - Wahyu Alpriyanti; Neni Hermita; Jesi Alexander Alim (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2022)
This research is a research and development that aims to develop the big book medium of conductor material in primary school with the 4D model (define, design, development and dissemination) proposed by Thiagarajan in 1974. This research uses descriptive quantitative method. The subjects of this study were 6 students from a public primary school in Pekanbaru. Research and development involves media experts as validators of the developed media. The data collection technique in this study was in the form of a validity and practicality questionnaire. The data analysis technique used in this study is to calculate the average percentage score seen from the aspects of content feasibility, presentation feasibility, language assessment, practicality of teacher and student responses. The results obtained from the media validity test show that the big book media conductor material is in the "very valid" category with a percentage score of 89.92%. While the results obtained from the practical test of teacher and student responses show that the big book media conductor material is "very practical" with a percentage score of  96.56%.